Development of Efficient Drive Based on Self-help - Németh, Géza; Péter, József (International Journal of Engineering and Management Sciences, 2019)
The efficiency and the life rating are essential characteristics of mechanical drives. The traction drives with proper geometry can avoid the geometrical slip and their efficiency can exceed that of the gear drives. The elements has hardened steel surfaces, the lubricant is rheopectic. There is no danger for thinning the oil film and consequently for connecting the asperities. The traction drives are relatively noiseless, they are applicable for increasing speed in particular. There are some problems to be solved in friction drive. This is the necessity of clamping force. A simple machine element usually make a constant clamping force, a tensioning mechanism can be too complicated. The ideal solution is a simple design which assure a clamping force that is proportional to the instantaneous external load requirements. The authors suggest a modified machine element – a helical torsion spring, an elastic one, instead of the original, rigid annular wheel – that comprises both the driving and clamping functions, and the latter one is proportional to the external load, so that the principle of self-help operates.